PENGARUH DISIPLIN KERJA KOMUNIKASI ORGANISASI DAN KOMPENSASI TERHADAP KEPUASAN KERJA PADA DIVISI DELIVERY CENTER PT POS INDONESIA CABANG CIMAHI - Meltareza, Ridma (Jurnal Common, 2023)
This study aims to investigate the influence of Work Discipline, Organizational Communication, and Compensation on Job Satisfaction in PT Pos Indonesia Delivery Center Division, Cimahi Branch. The research method used is a quantitative approach with a descriptive and verification approach. Data were collected through questionnaires from 100 respondents, employees of PT Pos Indonesia Delivery Center Division, Cimahi Branch, and analyzed using descriptive analysis and regression analysis. The results of the study indicate that Job Satisfaction, Work Discipline, Organizational Communication, and Compensation in PT Pos Indonesia Delivery Center Division, Cimahi Branch are categorized as less satisfactory. The average scores for Job Satisfaction, Work Discipline, Organizational Communication, and Compensation fall below the threshold value for the good category, which is 78. Regression analysis shows that there is a significant influence between the variables of Work Discipline, Organizational Communication, and Compensation on Job Satisfaction. Partial coefficient determination results reveal that Work Discipline has the most significant influence on Job Satisfaction, with a percentage of 90.2%. Organizational Communication also has a significant influence on Job Satisfaction, with a percentage of 78.7%. Meanwhile, Compensation has a 66.1% influence on Job Satisfaction. The simultaneous coefficient determination test shows that the combined effect of Work Discipline, Organizational Communication, and Compensation significantly influences Job Satisfaction, with a percentage of 93.1%. The remaining 6.9% is influenced by other factors outside of this study. Based on the research findings, the company needs to improve the quality of Work Discipline, Organizational Communication, and Compensation to create a more satisfying and motivating work environment for employees to achieve better job satisfaction.